CAPTIVATING GOD’S HEART: A HISTORY OF INDEPENDENT CHRISTIANITY, FUNDAMENTALISM, AND GENDER IN CHIN LIEN BIBLE SEMINARY AND THE SINGAPORE CHRISTIAN EVANGELISTIC LEAGUE, 1935-1997 - SIM DAO WEI, JOSHUA (2015)
Master's